Examination of the mechanical and physical characteristics of geopolymer composites reinforced with sisal fibers - Zerihun Getachew Debena; Dilinesaw Bogale Ayenew; Melese Yalew Ayalew; Dawit Damtew Darza; Gezahagn Gebre Geleso; Ewnetu Getu Beyene (Materials Research Express)
This paper aims to investigate and characterize lightweight sisal fiber(SF)-reinforced geopolymer composite (SFRGC) materials to utilize instead of cement-based construction materials. The investigation targets the impact of independent factors on the compressive, splitting tensile strength, and water absorption of fiber-reinforced geopolymer composite. A Response Surface Methodology(RSM) with box Behnken design(BBD) was used for characterization and to obtain the significance level of the selected variables such as fiber volume (5%, 10%, and 15%), fiber length in mm (5, 20, and 35), and alkali concentration (8 M, 12 M, and 16 M). Best result for compressive strength was 21.5 Mpa with a respective interaction of variables fiber volume, fiber length, and alkali concentration (5%, 20 mm, and 8 M). The best result for splitting tensile strength was 4.6 Mpa respective interaction of variables of (15%, 35 mm, and 12 M) respectively. Best result for water absorption was 5.325% with the interaction of variables of (5%, 20 mm, and 8 M).